Knowledge, attitude and practice of family caregivers on pressure injury prevention for community-dwelling older adults: a cross-sectional study in an Indonesia City - Sheizi Prista Sari; Irma H. J. Everink; Christa Lohrmann; Yufitriana Amir; Eka Afrima Sari; Ruud J. G. Halfens; Jos M. G. A. Schols (BMC Nursing)
Abstract Background Older adults in Indonesia are mostly living at home with their families. Informal care provided by family caregivers is essential to prevent older adults from getting pressure injuries (PIs). The objectives of this study were to examine the knowledge, attitude and practice of family caregivers regarding PI prevention among community-dwelling older adults in Indonesia. Methods A cross-sectional survey was conducted involving 267 family caregivers randomly selected from a population list provided by municipalities in Bandung, West Java, Indonesia. The study utilized the paper-based Knowledge, Attitude, and Practice on Pressure Injury (KAP-PI) questionnaire. Descriptive analyses (i.e. percentage, mean and standard deviation) were used to present participants’ scores in each domain based on their characteristics or categories and scores in every single item of questions or statements. Bivariate comparison analyses were conducted using independent t-test or ANOVA test to compare scores and a Chi-square was run to check correlations between knowledge, attitude and practice domains. Results This study show that more than half of the participants (61.0%) had insufficient knowledge about PI prevention, but nearly all participants (94.4%) had a positive attitude toward PI prevention for their older relatives. Still, 41.2% of the participants had inadequate practice on PI prevention. A correlation analysis revealed that having sufficient knowledge and a positive attitude towards PI prevention were positively correlated with practice (p < .05). Conclusion This study highlights a significant gap in family caregivers’ knowledge and practice regarding pressure injury (PI) prevention, despite their generally positive attitudes toward the care of older relatives. The findings are the initial diagnosis to guide educational strategies. Research should be performed to explore effective educational materials and an education program and also the necessary professional support to strengthen family caregivers’ role in PI prevention.